Is the central binary system of the planetary nebula Henize 2-428 a type Ia supernova progenitor? - García Berro, Enrique (2016)
We critically discuss the recent observations of the binary system atthe center of the bipolar planetary nebula Henize 2-428. We findthat the proposed explanation of two equal-mass degenerate objects witha total mass larger than the Chandrasekhar limiting mass that supposedlywill merge in less than a Hubble time, possibly leading to a SN Ia,is controversial. This hypothesis relies on the assumption that thevariability of the He II 5412 Å spectral lineis due to two absorption components. Instead, we propose that it can beaccounted for by a broad absorption line from the central system on topof which there is a narrow emission line from the nebula. This promptedus to study if the binary system can be made of a degenerate star and alow-mass main sequence companion, or of two degenerate objects ofsmaller mass. We find that although both scenarios can account for theexistence of two symmetric broad minima in the light curve, the secondone agrees better with observations. We thus argue that the claim thatHenize 2-428 provides observational evidence supporting thedouble-degenerate scenario for SN Ia is premature.